Characteristic of combined banana plant residue with different type of manure in pit compost - Nur Syahidah Azman,
Composting has been defined as intense microbial activity leading to decomposition of most biodegradable materials, usually mixtures of organic materials, which results in organic residue stability. Since banana plant residue is abundantly in one of UPM's community project at experimental site at Penjara Dusun Dato' Murad, one of the way to reap benefit from banana plant residue and reduce potential of pest source is by composting and turning it into organic fertilizer. To date, there is no study about the efficacy of pit (anaerobic) or semi aerobic composting of banana plant residue-based wastes moreover with manure as catalyst. Therefore, the objective of this study is to produce compost material from banana plant residue with most suitable composting catalyst which is chicken manure, goat manure, elephant manure, moringa leaves and also urea that has the best compost characteristic. The method used in this study is pit compost method and analysis of C:N ratio, pH, temperature, nutrient contents, and decomposition period in site project and laboratory for three month sampling. The results shown that the characteristic of composting process m composting banana plant residue from all treatments showed changes of pH near to neutral, stable moisture content around 40-60% which is the optimum temperature and stable C:N ratio for the manure as compost catalyst for compost after three month of decomposition and also temperature variation that show different stage of different treatment achieving their own mesophilic phase and thermophilic phase after three month of decomposition.